Iı. Abdülhamid Dönemi Nde İstanbul Bahçeleri (1876-1909) - Altıner, Fikriye Pınar (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, II. Abdülhamid Dönemi’nde, II. Abdülhamid’in yaptırılmalarında ve uygulanmalarında birinci dereceden etkili olduğu bahçe tasarımları incelenmiştir. Bahçelerden bazıları; Yıldız Sarayı Bahçesi, Maslak Kasırları Bahçesi, Huber Korusu, Taksim Bahçesi, Tepebaşı Bahçesi’dir. Bahçeler konum, tasarım özellikleri ve bileşenler, bitki çeşitliliği ve günümüzdeki durumları açısından incelenmiştir. Kaynaklarda bulunmayan görsel malzemeyi desteklemek amacıyla güncel fotoğraflar ile çalışma desteklenmiştir. Çalışmanın sonucunda 19. yüzyılda Avrupa’daki tarihi bahçeler ile II. Abdülhamid Dönemi’nde uygulanmış olan önemli tarihi bahçeler karşılaştırılmıştır.

In this study, the garden designs which were applied and constructed with the orders of Abdulhamid II were researched and analyzed. Gardens of Yıldız Palace, Maslak Pavilions, Huber Kiosk, Grand Champs de Morts, Petit Champs de Morts were some of the examples of the gardens that had researched through the study. The conditions both current and past, the characteristics of design and the vegetation envantory of the gardens has been examined and analyzed. Inscriptive references were supported by visual references which were the photograps that has been taken in the current time. As a conclusion, garden designs which were applied and constructed with the orders of Abdulhamid II has been evaluated briefly and they are compared with the garden designs in Europe at the 19th century.
Gardens Of Istanbul During The Reign Of Abdulhamid Ii (1876-1909)
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2008
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2008
Keywords: II. Abdülhamid; İstanbul; Bahçeler; Doğal Bahçeler; Yıldız Sarayı; Maslak Kasırları; Huber Korusu; Taksim Bahçesi; Tepebaşı Bahçesi.; Abdulhamid II; Gardens of Istanbul; Landscape Gardens; Yıldız Palace; Maslak Pavilions; Huber Kiosk; Grand Champs de Morts; Petit Champs de Morts.